Patterns of resource allocation in different habitats of Kalimeris intergrifolia in Northeast China - Yuan, Z. N.; Lu, J. M.; Chen, J. Y.; Jiang, S. Z. (Spanish Journal of Agricultural Research, 2011)
Understanding parameters that drive plant resource allocation for reproduction in potentially economically and environmentally important species, such as Kalimeris intergrifolia, is essential to maximize production rates. Hence, this study evaluates the characteristics in reproductive resource allocation of two K. intergrifolia communities at a saline-alkali open meadow and at a semi-enclosed secondary broad-leaved forest fringe, in the Songnen plains region of northeast China. Ramets from each habitat type were sampled at three intervals during the ripening stage (June-October). Relative resource distribution was quantified by measuring the dry weight of the above-ground ramet components, including the stem, leaf, corymb and seeds. The results indicated high variability in the distribution of resource allocation for both types, with larger phenotypic plasticity being recorded for the forest fringe than the open meadow. However, the allocation of resources into reproductive organs was higher in the open meadow than in the forest fringe, demonstrating that the open community was advantageous to the reproduction. Furthermore, our results indicate that biomass accumulation determines plant reproductive functioning. However, as resource allocation for reproduction increases, the biomass of above-ground ramet components decreases. Allometry exists in the K. intergrifolia populations when plants are in the ripening stage. Therefore, the future studies will focus on the mechanism of allometry. In conclusion, our study indicate that habitat parameters influence the general quantity of resources utilized for reproduction in this species, suggesting that open habitats should be preferentially targeted for optimal commercial application.